223k views
5 votes
-13 + 2m = 6 + 5m + 8

User Emad Feiz
by
4.9k points

1 Answer

5 votes

We are given the following expression


-13+2m=6+5m+8

We are asked to simplify the expression.

Step 1:

Combine the like terms together (meaning that constant terms on one side and variable terms on the other side)


-13-6-8=5m-2m

(Please note that whenever we shift a term from one side to another then the sign of the term is reversed)

Step 2:

add or subtract the like terms


-27=3m

Step 3:

Finally, find the value of the variable.


\begin{gathered} 3m=-27 \\ m=-(27)/(3) \\ m=-9 \end{gathered}

Therefore, m = -9 is the simplified form of the given expression.

User Alexander Shutau
by
4.7k points